Pre-camber control of large-span prestressed concrete continuous rigid-frame bridges under cantilever construction - Yingying Zhou (Archives of Civil Engineering)
In the commonly used cantilever construction method, the construction is greatly affected by the linearity and stress control, and the failure of linearity and stress control will lead to the deformation of the bridge. To solve this problem, the study carried out finite element analysis modeling of large-span prestressed concrete continuous rigid bridge, and measured the creep coefficient by creep test to determine the model parameters. The experimental results show that. When the self weight of concrete is 1.10γ. At that time, the deflection variation at the cantilever end of the main beam reached its maximum value near the mid span and side span merging sections, which were 8.6 mm and 9.7 mm, respectively. In the max cantilever state, increasing the concrete capacity decreases the compressive stress at the upper and lower edge of the cross-section to 1.18 MPa and 1.24 MPa, respectively. In the bridge-forming state, increasing the concrete deadweight results in a decrease in the normal stress at the upper and lower edges of the bridge to 1.24 and 1.27, respectively, while the normal stress at the lower edge of the cross-section remains unchanged. The creep modification model obtained from the creep test is able to predict the deformations and stresses of the cantilevered construction of a continuous rigid bridge with a more accurate prediction.